TERAPI âAKU BISA DAN AKU BERANIâ UNTUK MENINGKATKAN KOMUNIKASI VERBAL DAN NONVERBAL PADA ANAK MUTISME SELEKTIF - , ELY PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Selective Mutism (consistent failure to speak in specific social situations) usually found in children at school age. This study aims to improve the children verbal and nonverbal communication in social situations when they are at school and in the neighborhood. This study uses a single case ABA experiment with 4 times measurement of variables, which are pre-intervention, intervention, post-intervention and follow-up. Characteristics of the chosen subject are the subject had been diagnosed Selective Mutism, female, and studying at elementary school. Subjects received 11 sessions of behavior therapy with shaping method, positive reinforcement and fading stimulus, all are packaged in \"Aku Bisa dan Aku Berani\" Therapy. Measurements were made through observation and interviews (with parents and classroom teachers). Research questions posed in this study is whether the \"Aku Bisa dan Aku Berani\" therapy can improve verbal and nonverbal communication of Selective Mutism child in their social situations? The research question was tested by using visual inspection and qualitative analysis based on documents obtained during the therapy process (verbatim interviews and observation notes). The results showed there were developments in verbal and nonverbal communication to therapist and peers in the neighborhood, but there is no improvement in verbal and nonverbal communication to teacher at school.